2019
DOI: 10.1089/thy.2018.0436
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Hypothyroidism Restores Cold-Induced Thermogenesis in Humans

Abstract: Background: Hypothyroidism is a frequent endocrine disorder with common symptoms of increased cold sensitivity and unintended weight gain, indicating changes in energy expenditure (EE) and response to cold exposure. Thyroid hormones (TH) play an important role for proper function of brown adipose tissue (BAT) and cold-induced thermogenesis (CIT) in rodents, but the role of hypothyroidism on CIT in humans is uncertain. Methods: This was a prospective observational study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…Previously, we and others were able to demonstrate that REE is reduced in hypothyroidism and that restoring euthyroidism normalizes REE in humans (17,28). Here, higher levels of free T4 within the reference range did not lead to higher REE at room temperature in euthyroid individuals, which is in line with a recent study in a larger cohort (29).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previously, we and others were able to demonstrate that REE is reduced in hypothyroidism and that restoring euthyroidism normalizes REE in humans (17,28). Here, higher levels of free T4 within the reference range did not lead to higher REE at room temperature in euthyroid individuals, which is in line with a recent study in a larger cohort (29).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the main stimulus of CIT in adult humans appears to be cool environmental temperatures ( 21 , 35 , 36 ). Previously, we could demonstrate that in hypothyroid individuals the effect of environmental temperatures on CIT seems to be abrogated ( 17 ). Therefore, we would like to speculate that thyroid hormones facilitate the dynamic adaptations to cool temperatures also in humans.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…TH plays a critical role in thermogenic response to the cold. TH replacement in hypothyroid patients significantly increases energy expenditure at room temperature and even more during mild cold exposure [87]. However, a study with thyroid cancer patients undergoing thyroidectomy showed that TH replacement did not consistently increase energy expenditure [88], possibly due to suppression of catecholamine synthesis and adrenergic response in the hyperthyroid state [88,89].…”
Section: Th Increases Mitochondrial Biogenesismentioning
confidence: 99%
“…Thyroid hormone regulates the basal metabolic rate and energy expenditure. Cold-induced thermogenesis is higher in euthyroid compared to hypothyroid individuals 39 .…”
Section: Fat Tissue and Thermogenesismentioning
confidence: 89%